2016
DOI: 10.1016/j.jinsphys.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine exposure affects longevity, development time and body size in Drosophila melanogaster

Abstract: Atrazine is the one of the most widely used herbicides in the United States and non-target organisms may encounter it in the environment. Atrazine is known to affect male reproduction in both vertebrates and invertebrates but less is known about its effects on other fitness traits. Here we assessed the effects of five different chronic exposure levels on a variety of fitness traits in Drosophila melanogaster. We measured male and female longevity, development time, proportion pupated, proportion emerged, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 80 publications
1
16
0
2
Order By: Relevance
“…Paternal atrazine exposure was found to significantly decrease interactions with a mirror (a proxy for aggression) in male and female offspring from the 0.3ppb and 30ppb treatment. The lack of a significant decrease in aggression in the 3ppb treatment offspring (though the decrease was marginally non-significant) may be due to the non-monotonic nature of atrazine as found in other studies [3,[115][116][117][118]. For instance, Shenoy et al [3,68] found that male guppies prenatally exposed to 1 ppb were consistently less aggressive (within a mating context) than those prenatally exposed to 15 ppb.…”
Section: Plos Onementioning
confidence: 69%
“…Paternal atrazine exposure was found to significantly decrease interactions with a mirror (a proxy for aggression) in male and female offspring from the 0.3ppb and 30ppb treatment. The lack of a significant decrease in aggression in the 3ppb treatment offspring (though the decrease was marginally non-significant) may be due to the non-monotonic nature of atrazine as found in other studies [3,[115][116][117][118]. For instance, Shenoy et al [3,68] found that male guppies prenatally exposed to 1 ppb were consistently less aggressive (within a mating context) than those prenatally exposed to 15 ppb.…”
Section: Plos Onementioning
confidence: 69%
“…A lot of studies in other insects showed that pesticides can lead to morphometric variations. Marcus and Fiumera (2016) showed that exposure to atrazine, the one of the most widely used herbicides significantly affected male and female adult body size of Drosophila melanogaster. In Pterostichus melasitalicus, a carabidae, morphometric analyses also showed that dimethoate application caused a reduction in body or elytra lengths in females (Giglio et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in drosophilids observed developmental and genotoxic effects (81,82), which prompted Figuera et al (63) to investigate if these effects were owed to oxidative stress. To do that, they exposed the embryos (newly fertilised eggs) of the fruit fly Drosophila melanogaster to atrazine concentrations ranging between 10 and 100 µmol L -1 through diet until they developed into adult flies.…”
Section: Involvement Of Oxidative Stress In Atrazine Toxicitymentioning
confidence: 99%